Reseña de: The Scramble for the Amazon and the “Lost paradise” of Euclides Da Cunha (Hetch, 2013) (2017)
Sussana Hetch (2013). The scramble for the Amazon and the “Lost paradise” of Euclides Da Cunha. Chicago – London: The University of Chicago Press. 613 pp. isbn: 13:978-0-226-32281-0.